Tradisi Baritan Masyarakat Muslim Pedesaan Wonosobo: Dialektika Komunitas-Struktur Perspektif Victor Turner - Muhammad Yusuf; Sri Rahayu; Muhammad Amin (KURAS Institute, 2023)
This paper aimed to reveal the meaning and relationship of community-structure dialectics through the Baritan tradition carried out by Muslim communities in Jojogan Village, Parikesit Village, Patak Banteng Village, Wonosobo Regency. The participants in this research are Muslim communities in Jojogan Village, Patak Banteng Village, and Parikesit Village who carry out the Baritan tradition. Participants in the community were classified into ordinary people, community leaders, religious leaders, and village officials. The data collection technique was carried out by collecting research data obtained through interviews and observation methods. The results showed that in the tradition there are symbols that build egalitarian social relations where individuals merge and release their social status and these symbols have meanings that are understood together. The symbols and meanings can be seen in the activities of cleaning springs, praying together, and alms which are a series of Baritan tradition ceremonies. Second, the Baritan tradition is a form of community resistance to the life of the general public that creates a hierarchical structure or relationship in social life which is considered to eliminate or threaten the way of life that is in accordance with local values.